Pengaruh Efektivitas Pengendalian Internal, Kesesuaian Kompensasi dan Moralitas Individu Terhadap Kecenderungan Kecurangan Akuntansi Studi Kasus pada BKD Kabupaten Boyolali - Ditya Renni Prastiwi; Sri Laksmi Pardanawati; Maya Widyana Dewi (Jurnal Ilmiah Keuangan Akuntansi Bisnis (JIKAB), 2023)
This study aims to determine the effect of the effectiveness of internal control, compensation suitability, individual morality on the tendency of accounting fraud. The sampling technique in this study used a purposive sampling technique. The method of data analysis in this study used the multiple linear regression analysis method with the SPSS program. The data analysis method consisted of descriptive statistical test, data quality test and classical assumption test. This study uses hypothesis testing consisting of multiple linear regression test. Based on the results of this study indicate that the effectiveness of internal control has a significant effect on the tendency of accounting fraud, the suitability of compensation has a significant effect on the tendency of accounting fraud. While individual morality does not have a significant effect on the tendency of accounting fraud. Keywords: Accounting Fraud Tendency, Compensation Suitability, Individual Morale, Internal Control Effectiveness